Modulation of Nrf2/HO-1 by Thymoquinone During Cisplatin-Induced Nephrotoxicity - Ulu, Ramazan; Dogukan, Ayhan; Tuzcu, Mehmet; Gurel, Ali; Muqbil, Irfana; Mohammad, Ramzi M.; Şahin, Kazım (Turk Nefroloji Diyaliz Transplantasyon Dergisi, 2013)
OBJECTIVE: Side effects of cisplatin, such as nephrotoxicity, limit its use in chemotherapeutic regimens and indicate an agent that suppresses its toxicity. Thymoquinone (TQ), the predominant bioactive constituent present in black seed oil (Nigella sativa), has antiinflammatory, antioxidant and antitumor effects. We propose a protective mechanism of of TQ on cisplatin-nephrotoxicity in rats that is through modulation of Nrf2-mediated antioxidant induction and reduced inflammation. MATERIAL and METHODS: Twenty-eight male Wistar rats (8 weeks-old) were divided into four groups; Control (vehicle; 0.9% saline, 1 ml/kg body wt., p.o.), TQ (10 mg/kg body weight/day in drinking water for 5 days), cisplatin (a single injection of 7mg/kg body wt, i.p.) and TQ for 5 days in drinking water then a single injection of cisplatin. On day 10, all rats were sacrificed by cervical dislocation, kidneys were removed, and serum urea and creatinine were collected. RESULTS: Serum urea and creatinine levels were significantly higher in cisplatin-treated rats compared with control rats. TQ-treatment significantly decreased serum urea and creatinine levels. Cisplatin-treatment caused significant downregulation of the nuclear NF-E2-related factor-2 (Nrf2), heme oxygenase-1(HO-1) and caused an increase in the levels of nuclear factor-kappa B (NF-ae B). Interestingly, TQ supplementation significantly improved the changes associated with cisplatin nephrotoxicity by increasing the levels of Nrf-2 and HO-1 and decreasing the levels of NF-ae B. CONCLUSION: This study demonstrates the TQ targets NRF2/HO-1 and can be used as a potential agent against cisplatin-induced nephrotoxicity.
Keywords: Cisplatin; Kidney; Nrf2; HO-1; Thymoquinone